Correct, (ignoring that you put a 0.25 instead of 1 0.75)a3 = a2 - 1/4*a1, a3 = 1 - 1/4*1 = 0.25???
Hello
Given this:
an = a(n-1) - 1/4A(n-2)
Where n is an element of N (any whole number, 0,1,2,3...)
a1 = a2 = 1
Create a table with A1, A2, A3, A4, A5 and their answers.
Then prove that the explicit formula is:
An = n(1/2)^n-1
My shot at it:
The thing that I am stumped on:
a1 = a2 = 1
Does this mean that for all N's the answer is 1?
a3 = a(n-1) - 1/4A(n-2)
a3 = a2 - 1/4*a1, a3 = 1 - 1/4*1 = 0.25???
The prize for doing math at 6 am after a night in the C++ language.
1-0.25 = 0.75!
Thanks a ton, but how do I prove or not prove that the formula can be written as:
An = n(1/2)^n-1?
I mean, doing so leaves me with the same answers... so the formula is correct, but proving it???
Of course I could write it with words, explaninig why, but that does not prove it? hmm...